Implementation of Biopore Infiltration Holes in Increasing Soil Permeability in Sungai Langka Village - Meysha Azhara; Irhamni Irhamni; Fajriharish Nur Awan; Aulia Annas Mufti; Yuni Lisafitri; Bambang Prasetio; Sillak Hasiany; Tastaptyani K. Nufutomo; Alfian Zurfi; Dian Neli Pratiwi (Jurnal Inovasi Pendidikan dan Sains, 2025)
This study aims to improve low soil absorption capacity by implementing biopore infiltration hole technology to reduce waterlogging and increase groundwater availability, especially during the dry season. This biopore infiltration hole technology can create additional pores, allowing rainwater to infiltrate more rapidly. The method used was a field experiment with five soil samples taken from Dusun II, Sungai Langka Village. The biopore infiltration holes were constructed to a depth of 100 cm and a diameter of 10 cm, and soil permeability was measured using the falling head method before and after installation. This method was selected because it is suitable for fine-grained soils with low absorption capacity. Observations were conducted for 14 days to monitor changes in the soil permeability coefficient driven by variations in moisture, microbial activity, and the decomposition of organic materials within the hole. The study found a significant increase in the soil permeability coefficient after the application of biopore infiltration holes. The highest increase occurred at sample point 5, where the permeability coefficient rose from 11.9 cm per hour to 45.7 cm per hour. In conclusion, the application of biopore infiltration holes effectively improves soil pore structure and enhances soil water-absorption capacity, providing an alternative solution for water management and reducing waterlogging in residential areas